Digital Transformation in Accounting: Peran Accounting Information Systems dalam Mendorong Aksesibilitas Data - Aulia, Suci; Sivano, Tamara Theresia; Purnomo, Didik Heri; DP, Rina Tjandra Kirana (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This research explores the impact of digital transformation on Accounting Information Systems (AIS) with a specific focus on improving data accessibility in the modern financial environment. The rapid advancement of digital technologies has encouraged organizations to adopt more sophisticated and integrated accounting systems to support faster and more transparent financial reporting. By utilizing a systematic literature mapping approach, this study analyzes 27 peer-reviewed articles published between 2021 and 2026 in order to synthesize current technological developments, implementation strategies, and structural challenges related to the digitalization of accounting systems. The findings reveal that the integration of emerging technologies such as Artificial Intelligence (AI), cloud computing, and blockchain plays a crucial role in enhancing the efficiency, reliability, and accessibility of financial data. These technologies enable real-time financial transparency, improve operational intelligence, and strengthen internal control mechanisms within organizations. Furthermore, the study shows that digital technologies can significantly accelerate the distribution of accounting information and potentially reduce fraud risks by up to 85 percent. However, the effectiveness of these technologies is not determined solely by technical capabilities. Non-technical factors, including organizational culture, digital readiness, employee competence, and the presence of technical debt, strongly influence the success of AIS implementation. Therefore, achieving optimal data accessibility requires a balanced synergy between advanced technological infrastructure and a proactive digital mindset within the workforce. These findings highlight the importance of modernizing accounting education curricula to address the growing digital skills gap and support sustainable digital maturity in the accounting profession.